Factors Related To The Suitability Of Contraceptive Use Among Active Family Planning Acceptors In Kayu Aro District, Jambi Province In 2023 - Sasra Juwita; Dwi Noerjoedianto; Budi Aswin; M. Ridwan; Ashar Nuzulul Putra (International Journal of Health Engineering and Technology, 2026)
The selection of appropriate contraceptive methods is a crucial factor in the success of a family planning (FP) program, as mismatching methods with needs, health conditions, and reproductive goals can increase the risk of unwanted pregnancy. This study aims to analyze factors related to the appropriateness of contraceptive use among active FP acceptors in Kayu Aro District, Jambi Province in 2023. The study used a quantitative analytical design with a cross-sectional approach on 106 active FP acceptors selected by simple random sampling. Data were collected using a structured questionnaire and analyzed univariately and bivariately. The results showed that the majority of respondents used appropriate contraceptive methods (88.7%). There was a significant relationship between the number of children (p=0.001), family planning goals (p=0.006; p=0.002), the role of health workers (p=0.001), community stigma (p=0.001), and information sources (p=0.001) with the appropriateness of contraceptive use, while age (p=0.505) and medical history (p=0.204) were not significantly related. It was concluded that the number of children, family planning goals, support from health workers, community stigma, and information sources were factors related to the appropriateness of contraceptive use. Strengthening contraceptive education, counseling by health workers, and providing accurate information are needed to improve the accuracy of contraceptive method selection.